Analisis penerapan process costing dalam industri manufaktur untuk meningkatkan efisiensi dan profitabilitas melalui hilirisasi - Rinayanti, Rinayanti; Irawan, Regita Aulia Indy; Wardana, Muhammad Daffa; Mariana Mariana; Diana, Diana (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The application of process costing in manufacturing industries has proven to provide significant benefits in cost management, especially in mass production with uniform products. This study aims to analyze the application of process costing in various industries, with a focus on sectors that utilize natural resources, and to explore the optimization of this method to improve efficiency and profitability through downstream processing. The research method used is a literature review, gathering relevant publications from the last 10 years, including articles and research reports, through searches in academic databases such as Google Scholar and JSTOR. The findings indicate that while process costing is effective in controlling costs and improving efficiency, this method has limitations in handling varied products and custom orders. However, in the downstream processing of natural resources, the application of process costing can be key in managing costs during the transformation of natural resource products into higher-value downstream products. The final report includes a critical analysis of the application of process costing in natural resource-based industries, along with a discussion of the practical implications and the importance of this method for management in making strategic decisions to achieve sustainability and profitability. This study provides comparative insights that are useful for industries in optimizing the application of process costing to enhance performance, competitiveness, and profitability through downstream processing of natural resources.